Calculation For Multipole Mixing Ratios OF Gamma Transitions From Deformation Levels IN 152Sm Nucleus - Hady, F.1\’1. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In the present work , the a2 - ratio method has been used to calculate the multipole mixing ratios , 5 - values • of y - transitions from excited levels of deformation nucleiL-. ( 152Sm ) . The results obtained confirm the validity of this method in calculating the o - values . The present results are in good agreement with those of the experimental results, ref.( I ,2) , and of theoretical results using interaction boson model (IBM-I) ,ref. (5).